2010
DOI: 10.1177/0009922810379040
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Outcomes of Pierre Robin Sequence: An Institutional Experience

Abstract: Neonates with PRS who do not require surgical airway intervention are more likely to require assisted feeding, have slower weight gain, and a shorter average hospital stay compared to neonates undergoing mandibular MDO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…The proportion of sPRS (14.6%) was similar to the findings of Bü tow et al [10]. Other authors described higher numbers of syndromic diagnoses between 27 and 46% [11,12]. These findings are somewhat unexpected since 91.7% of all patients were examined by a geneticist and underwent genetic testing in the search for syndromes.…”
Section: Diagnosticssupporting
confidence: 84%
See 2 more Smart Citations
“…The proportion of sPRS (14.6%) was similar to the findings of Bü tow et al [10]. Other authors described higher numbers of syndromic diagnoses between 27 and 46% [11,12]. These findings are somewhat unexpected since 91.7% of all patients were examined by a geneticist and underwent genetic testing in the search for syndromes.…”
Section: Diagnosticssupporting
confidence: 84%
“…This was done by means of a search of the Leuven Multidisciplinary Cleft database, identifying 48 PRS patients and 314 CP patients over an 11 year period. Subsequently, the medical records of the PRS patients were retrospectively analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of major surgery-related adverse effects in our two patients treated with distraction osteogenesis agrees with that previously reported for other syndromic patients with micrognathia phenotype. In their retrospective review, AlSamkari [17] reported successful outcomes regarding upper airway and feeding management in patients with PRS independently of the syndromic status of the patients. Similarly, Taub et al, reported successful distraction for the hypoplastic mandible in patients with muscular dystrophy and amniotic band sequence, settings known to induce pathologic changes in the native bone [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…table 6). These children are sometimes grouped with syndromic PRS [Shprintzen, 1988[Shprintzen, , 1992Marques et al, 1998;Cruz et al, 1999;van den Elzen et al, 2001;Li et al, 2002;Printzlau and Andersen, 2004;Evans et al, 2006;de Buys Roessingh et al, 2007;Izumi et al, 2012;Patel et al, 2012;Gomez-Ospina and Bernstein, 2016] but also grouped with nonsyndromic children in other studies [Sheffield et al, 1987;Bütow et al, 2009;Al-Samkari et al, 2010]. These differences in classification of the PRS-Plus group make interstudy comparisons challenging.…”
Section: Phenotypic Spectrum Of Children With Nonsyndromic Prsmentioning
confidence: 99%